Seeking Peace by any means Possible: An Assessment of the Role Civilian JTF in Crime Management in North-East Nigeria - Agwanwo, Destiny Eze; Ejovi, Stephen Ohurhu (NIU Journal of Social Sciences; Vol 11 No 1 (2025): NIU Journal of Social Sciences, Vol. 11 No. 1, March 2025DO - 10.58709/niujss.v11i1.2139, 2025)
Crime and insecurity have been, and continue to be one of the major challenges confronting the nation, with the north-eastern part assuming a permanent theater of war between the Boko Haram terrorist group and the Nigerian state since 2009. This paper presents an assessment of the role the Civilian JTF in the fight against terrorism in Borno State. To execute this study very effectively, the following objectives have been pursued: (1) the examination of the role Civilian JTF in crime management (2) investigation of how effective they are in crime management and (3) the exploration of the strategy/method employed in carrying out their informal crime management function. This paper gathered data qualitatively. The qualitative data was collected through Key Persons Interviews (KPI) of some purposively selected individuals. The data was subjected to thematic content analysis. The finding showed that the failure of the formal social control agencies has birthed the civilian JTF, that have complemented and filled the gap created in a way and they are also effective in crime management. The study recommends that the formal law enforcement agencies should collaborate with the Civilian JTF in the area of training and retraining, as well as, in information sharing. Furthermore, they - Civilian JTF - should be given incentives by the Government and Communities for the risky job they are doing. This will serve as motivation to do more for their communities. Keywords: Seeking Peace, Assessment, Role, Civilian JTF, Crime management, Northeast Nigeria